Protein Content Test of Tilapia Fish Extract (Oreochromis Mossambicus) before and after Freeze Dry Using Biuret Method - Walin; Hardono Susanto; Bagoes Widjanarko; Nurjazuli Nurjazuli (Institute of Medico-legal Publications Pvt Ltd, 2022)
Objective: To determine the difference in protein content of tilapia extract before and after drying process.Materials and Methods: This study was designed with a true experimental design. The research sample wastilapia fish extract with 3 replications in each sample. The measurement of protein content was carried out onsamples before and after drying. The drying process of tilapia extract was carried out for 48 hours using a freezedryer. Furthermore, the dried samples were tested for protein content using the biuret method supported by theUV-Vis Spectrophotometer instrument. The testing stages include making the standard solution, determining themaximum wavelength, determining the operating time, and making a standard curve.Results: Showed that the protein content of tilapia extract before and after drying was 2.23% and 27.4%,respectively. The results of statistical analysis showed that there was a significant difference between the proteincontent of tilapia fish before and after drying.Conclusion: There was an increase in protein content of tilapia fish extract after drying by 25.17%.